Peran Brand âKampoeng Batik Laweyanâ dalam Menguatkan Batik Laweyan Untuk Meningkatkan Daya Saing Industri Batik âKampoeng Batik Laweyanâ Solo - Basworo, Basworo; Sujadi, Sujadi (Benefit: Jurnal Manajemen dan Bisnis, 2018)
The existence of Laweyan Batik has been around since before 1500M (Mlayadipuro, 1984), with Laweyan Market and Bandar Kabanaran as a center of trade and sell of clothing material (lawe) of Pajang Kingdom which is busy and strategic at that time (Priyatmono, 2004). A visit to Laweyan proves that Laweyan is a batik area that has existed long ago, it can be seen from the form of buildings in the area (Aviarini Indrati, et al, 2011). The policy of Surakarta City Government has established Kampoeng Laweyan as a tourism area under the name of "Kampoeng Batik Laweyan", and the obligation of Civil Servant in wearing batik dress at certain time made the development of batik industry in Laweyan very good (Atiqa Sabardila, et al, 2008). Entrepreneurs in "Kampoeng Batik Laweyan" actually have been able to export to foreign countries, especially in Asia, Europe, Middle East and America. But most of them are still product without brand, so there is no increase in product competitiveness to enter international market with local brand. (Siti Rahayu Binarsih, et al, 2013). Brand Kampoeng Batik Laweyan, with the support of technology today, makes the site "Kampoeng Batik Laweyan" exists, in addition to expand the marketing area of the product, it also make easier for prospective of buyers. The data in this study were taken from all batik entrepreneurs in "Kampoeng Batik Laweyan" which amounted to 56 entrepreneurs by using questionnaires that have passed the validity and reliablitas test. After passed the classic assumption test include multicollinearity test, autocorrelation test, heteroscedasticity test and normality test, then multiple regression analysis and regression with moderation obtained result: 1) The variable Batik Laweyan Product Significantly Improve the Batik Industry Competitiveness "Kampoeng Batik Laweyan" in Kota Solo, 2) Brand "Kampoeng Batik Laweyan" is Significantly Influence on Improving Competitiveness of Batik in Industry Kampoeng Batik Laweyan in Solo, 3) Brand "Kampoeng Batik Laweyan" Significantly Strengthening the Laweyan Batik Effect in Improving Batik Industry Competitiveness "Kampoeng Batik Laweyan" Solo , So the three hypotheses proved to be true. The results of this study can be used as a reference in establishing policies about the development of "Kampung Batik Laweyan", it is very necessary to conduct research to sharpen the role of the brand (cluster branding) to batik industry competitiveness in both national and global markets.